Un posible caso de dimorfismo sexual en “venericardia” patagónica (Sowerby, 1846) (bivalvia: carditidae) - Perez, Damián (2017)
‘Venericardia’ patagonica is one of the most common bivalve species represented in the late Oligocene–middle Miocene of Patagonia. Previous authors recognized two contrasting morphologies within this species based on sculpture and outline. An Elliptic Fourier Analysis was performed, using the anterior view of 95 specimens. A Principal Component Analysis was carried out with the Fourier coefficients. The results show two well differentiated groups, based on development of the convexity, each of which could correspond to the mature male and female, as is proposed for other carditids. The females have more bulky shells, with maximum convexity at the centre of valves. The males have less bulky shells, with a sharp ventral edge. These differences correlate with sculpture (more pronounced in males) and size of specimens (larger in females).